Molecular characterization and phylogeny of Wolbachia pipientis in mosquitoes - Kusmintarsih, Endang Srimurni; Ambarningrum, Trisnowati Budi (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Wolbachia is an intracellular, maternally inherited bacteria that infect a wide variety of arthropods, including several mosquito such as Aedes albopictus , Armigerus , Culex , and Manzonia . However, until now there have been no reports of the existence of endosymbionts from several genera of mosquitoes from Indonesia. Therefore, we screen Wolbachia on several mosquito genera. The aim of the study was to determine the spreading of Wolbachia endosymbiont in mosquitoes from Indonesia. Mosquitoes were taken from various breeding and resting places, the captured mosquitoes were identified, the PCR product was carried out by gel electrophoresis. Visualization of amplicon bands under ultraviolet light. The result showed that the mosquitoes ( Manzonia, Aedes albopictus , and Armigerus ) tested were positive for the Wolbachia endosymbiont. Analysis phylogeny shows, that Wolbachia in three genus mosquitoes consists of two clades where the first clade consists of Wolbachia from Aedes albopictus and Manzonia, and the second clade consists of Wolbachia from Armigerus and other Wolbachia from some insects as outgroups. Subsequently, the phylogenetic trees based on the wsp revealed that Wolbachia from Aedes samples 1, 2, and Manzonia include monophyletic while Wolbachia from Armigerus is paraphyletic. Wolbachia from Armigerus close to Wolbachia from Tetranychus urticae.